Static : a novelization - Sorrells, Walter; MacHale, D. J.; Rogow, Stan. (New York : Grosset & Dunlap, 2006)
A charter plane crash on a deserted island forces a disparate group of teenagers to bury their petty jealousies and cooperate in an attempt to survive.
"Adapted from the teleplays by D.J. MacHale. Based on the TV series created by D.J. MacHale, Stan Rogow."
Keywords: Aircraft accidents; Islands